Cardiovascular Diseases and Associated Factors in a Middle-aged Population of Rupa Rural Municipality, Kaski, Nepal: A Community-based Cross-sectional Study - Bhandari, Tulsi Ram; Paudel, Grish; Paudel, Shishir; Chalise, Anisha; Khatiwada, Bhushan; Ojha, Jenny; Chapagain, Nawraj; Yadav, Uday Narayan (Journal of Health Promotion, 2024)
Cardiovascular diseases (CVDs) are the leading cause of mortality, not only posing pressure on health systems but also impeding the socio-economic development of Nepal. This study aims to assess the status of cardiovascular diseases (angina pectoris and myocardial infarction) and its associated factors among the middle-aged population of Rupa Rural Municipality, Nepal. A community-based cross-sectional study was conducted among 525 middle-aged (35-60 years) population of Rupa Rural Municipality, Nepal between August and December 2020 adopting simple random sampling. The WHO STEPS survey tool was used to collect the socioeconomic and behavioural characteristics, and the 10-item validated rose angina questionnaire (RAQ) to assess angina pectoris (AI) and myocardial infarction (MI). A multivariate logistic regression analysis was applied to identify the factors associated with AP and MI. The study respondents’ mean (SD) age was 47.29 (±8.354) years. The prevalence of AP and MI was 9.1% and 2.5% respectively. The prevalence of AP was significantly higher among those aged 55 and above (ORA:3.20, CI:1.41-7.29) and those consuming vegetables less than 4 days a week (ORA:2.15, CI:1.12-4.11) as compared to those aged 35-44 years and consuming vegetables ≥4 days a week, respectively. The prevalence of CVD events (MI and AP) has increased in Nepal. The risk of developing AP increases with age and among those respondents consuming vegetables less than four days a week. The findings of this study call for the implementation of CVD risk assessment intervention at the primary healthcare level for the early detection and prevention of cardiovascular disease. The study further emphasizes education initiatives to promote healthy diet habits and lifestyle modifications in rural areas, which may reduce the risks of CVDs.